Follicular Thyroid Carcinoma Metastasis to the Skull and Brain: Case Series with Literature Review (Bangladesh Journal of Nuclear Medicine, 2023)
Distant metastasis is more common in follicular thyroid carcinomas (FTC) than papillary thyroid carcinomas (PTC), as vascular invasion is often characteristic of FTC. Lung, bone, brain, liver, bladder, and skin are potential sites of distant metastases. On the other hand, lymph node involvement is much less common (8–10%) in cases of FTC compared to PTC. The therapy of patients may be significantly impacted by learning more about the epidemiological features of thyroid metastases at uncommon sites. In our experience, metastases in uncommon sites do not always indicate a poor prognosis for differentiated thyroid carcinoma (DTC), which might be due to the disease patterns. Every year, around 5% new FTC patients are registered, treated with radioiodine, and followed up in the thyroid division of National Institute of Nuclear Medicine and Allied Sciences (NINMAS). Four FTC patients (F=3, M=1) with skull bone and brain metastases are discussed in this case series. All of them were post thyroidectomized and were referred to NINMAS for radioiodine ablation therapy (RAIT). Two of them had skull and brain metastases, third patient had extensive skull, facial bone and pubic bone invasion, whereas, fourth patient had multiple skull metastases.Bangladesh J. Nuclear Med. 25(2): 128-137, 2022